Akbar the great emperor of India - Calza, Gian Carlo (Skira, 2012)
"An amazing exhibition catalogue showing the splendors of one of the greatest rulers of the world, India's Emperor Akbar (1542-1605). Akbar the Great is considered one of the most splendid sovereigns of humankind. Though he never learned to read or write, he was a great protector of poetry and literature, the builder of the grandiose capital Fathepur Sikri, the City of Victory, and the promoter of new movements in arts and crafts. The catalogue illustrates his deep art appreciation, detailing his court life with portraits and images of political activities, cultural events, and his military glory through arms and armor. Jewel boxes, turban ornaments, earrings, and necklaces are lavishly presented from the most important Indian, European, and American museums and collections. Although the author references the latest in art historical scholarship, this book is also aimed at readers with an affinity for Indian culture."